Respuesta :

Answer:

7. (2,1) 8. (8,2)

Step-by-step explanation:

Step: Substitute4z−7foryin5y+3z=11:

5y+3z=11

5(4z−7)+3z=11

23z−35=11(Simplify both sides of the equation)

23z−35+35=11+35(Add 35 to both sides)

23z=46 Divide both sides by 23

x=2

Substitute2forxiny=4z−7:

y=4z−7

y=(4)(2)−7

y=1

Step: Solve2x+4y=24for x:

2x+4y+−4y=24+−4y(Add -4y to both sides)

2x=−4y+24

x=−2y+12

−2y+12forxin−2x+8y=0:

−2x+8y=0

−2(−2y+12)+8y=0

12y−24=0(Simplify both sides of the equation)

12y−24+24=0+24(Add 24 to both sides)

12y=24 Divide both sides by 12

y=2

Substitute2foryinx=−2y+12:

x=−2y+12

x=(−2)(2)+12

x=8

ACCESS MORE